An audit and clinicopathological study of fibroepithelial lesions of the breast at a tertiary care centre and comparison with WHO grading - Yadav, Deepti; Meel, Mukta; Hemrajani, Deepika; Mittal, Aarti; Mathur, Kusum (International Surgery Journal, 2020)
Background: Mammary fibroepithelial lesions encompass a wide spectrum of tumors ranging from an indolent fibroadenoma to potentially fatal malignant phyllodes tumor (PT). The criteria used for their classification based on morphological assessment are often challenging to apply and there is no consensus as to what constitutes an adequate resection margin. The aims of the study were to study histopathological spectrum of fibroepithelial lesions of breast at tertiary care centre, to stratify and classify various fibroepithelial lesions into fibroadenomas and PT, reclassify all confirmed cases of PT seen in the study period according to standard histopathological WHO criteria. Methods: Records and slides of fibroepithelial lesions of the breast received at the department between January 2016 and August 2019 were retrieved and reviewed. Results: A total 891 fibroepithelial lesions of breast were diagnosed during this duration. Out of these, 826 (92.7%) were fibroadenoma and its variants, 34 (3.8%) cases were of fibroadenomatoid mastopathy and 31(3.5%) were PT. Among all PT, 8 (25.8%) were borderline and 4 (12.9%) were malignant, rest (61.3%) were benign. Conclusions: Fibroepithelial tumours of the breast are a heterogenous group of lesions ranging from fibroadenoma at the benign end of the spectrum to malignant PT. There are overlapping histologic features among various subtypes, and transformation and progression to a more malignant phenotype may also occur. Given the significant clinical differences within various subtypes, accurate pathologic classification is important for appropriate management. Although some immunohistochemical markers may be useful in this differential diagnosis, histomorphology still remains the gold standard.